Heavy Metal Contamination of Groundwater in the Tea Garden Belt of Darrang District, Assam, India. Issue Volume 6:Issue S1(2009) (2009) - Borah, K. K.; Bhuyan, B.; Sarma, H. P.
Abstract : A study has been carried out on heavy metal contamination of groundwater with respect to cadmium, manganese, zinc and copper in the tea garden belt of Darrang district, Assam, India. Heavy metals in groundwater are estimated by using Atomic Absorption Spectrometer, Perkin Elmer AA 200. Univariate statistics along with skewness, kurtosis and 't' test have been employed to test the distribution normality for each metal. The study reveals that the groundwater of the area is highly contaminated with cadmium. A good number of samples are also found to contain manganese at an alert level. The concentrations of copper and zinc in the groundwater of the area are within the guideline values of WHO. Statistical results show that all the metals under study exhibit an asymmetric distribution in the area with a long asymmetric tail on the right of the median. Keeping in view of the high concentrations of cadmium and manganese, it is suggested to test the potability of groundwater of the area before using it for drinking.